The Impact of Sex on the Response to Proton Pump Inhibitor Treatment - Holmfridur Helgadottir; Einar S. Björnsson (Pharmaceuticals, 2023)
Proton pump inhibitor (PPI) treatment is responsible for substantial gastrin elevation secondary to reduced intragastric acidity. Due to the increasing global prevalence of PPI users, concerns have been raised about the clinical significance of continuous gastrin elevation and its potential long-term side effects. Hypergastrinemia secondary to PPIs has trophic effects on gastric mucosa, leading to enterochromaffin-like cell hyperplasia and gastric (fundic) polyp formation, and it is believed to provoke acid rebound following PPI withdrawal that induces PPI overutilization. Previous studies have found higher gastrin release following PPI therapy in females compared with males, and sex differences have also been demonstrated in pharmacokinetic parameters and dose requirements for acid reflux. It is conceivable that females might be at increased risk of PPI overuse, because they often receive higher milligram-per-kilogram doses. The prevalence of PPI use is more common among females, and the female sex is a risk factor for adverse drug reactions. This non-systematic review outlines the current knowledge of the impact of biological sex on the response to PPIs. The aim is to highlight the female sex as a potential risk factor that could be a step toward precision medicine and should be considered in future research on the response to PPI treatment.